The Development of Accounting in Indonesia - Naimah, Naimah; Setiawan, Grace; Maulida, Yuliawati; Wibowo, Eko Prio; Kertamanggala, Lia (Indonesian Financial Review, 2025)
This study examines the historical trajectory of accounting development in Indonesia and how it has evolved through institutional reform, global convergence, and technological transformation. Using a qualitative historical approach and content analysis of academic and regulatory sources, the study identifies eight major phases of accounting evolution, from the colonial era to the digital transformation period. The findings reveal that Indonesia’s accounting development has been shaped by political transitions, economic reforms, and technological advances—particularly the adoption of International Financial Reporting Standards (IFRS) and automation systems. The study uniquely integrates institutional change theory and global convergence theory to explain how domestic accounting practices internalize international norms while retaining local identity. This research contributes to accounting historiography in emerging economies and highlights the strategic role of accountants in digital governance, education, and sustainable professional development.